Allostery at a protein-protein interface harboring an intermolecular motional network - Medina Gomez, Sara; Gonzalez, Tye I.; Vasa, Suresh K.; Linser, Rasmus (Technische Universität Dortmund, 2024)
Motional properties of proteins govern recognition, catalysis, and regulation. The dynamics of tightly interacting residues can form intramolecular dynamic networks, dependencies fine-tuned by evolution to optimize a plethora of functional aspects. The constructive interaction of residues from different proteins to assemble intermolecular dynamic networks is a similarly likely case but has escaped thorough experimental assessment due to interfering association/dissociation dynamics. Here, we use fast-MAS solid-state 15N R1ρ NMR relaxation dispersion aided by molecular-dynamics simulations to mechanistically assess the hierarchy of individual μs timescale motions arising from a crystal-crystal contact, in the absence of translational motion. In contrast to the monomer, where particular mutations entail isolated perturbations, specific intermolecular interactions couple the motional properties between distant residues in the same protein. The mechanistic insights obtained from this conceptual work may improve our understanding on how intramolecular allostery can be tuned by intermolecular interactions via assembly of dynamic networks from previously isolated elements.
Angewandte Chemie / International edition; 63(47)
Keywords: Solid-state NMR spectroscopy; Protein dynamics; Dynamic networks; Allostery; 540; Festkörper-NMR-Spektroskopie; Protein-Protein-Wechselwirkung; Molekularbewegung; Allosterie